Analisis Hukum Perdata dan Hukum Fiqih Terhadap Pencegahan Perkawinan di Bawah Umur dengan Tujuan Menciptakan Kerukunan Rumah Tangga - Lilis Handayani (Journal of Legal and Cultural Analytics, 2022)
This study aims to describe the analysis of civil law and fiqh law on the prevention of underage marriage with the aim of creating domestic harmony, the purpose of this study is to educate readers to carry out marriage at the age set by the government, this type of research is qualitative which seeks to reveal phenomena that are developing in the present time, data collection techniques include observation, unstructured interviews, after the data is obtained, an in-depth analysis is carried out. Based on the results of the study, it has been found that the age of marriage must follow the provisions set by the government, the triggers for early marriage are family factors, digital technology factors, promiscuity factors and cultural factors. Civil law instruments have been regulated by regulations and legal mechanisms that have been set by the government, while fiqh law must fulfill the pillars of marriage.